2014
DOI: 10.1002/prep.201300152
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5‐(1H‐Tetrazolyl)‐1‐hydroxy‐tetrazole and Energetically Relevant Nitrogen‐Rich Ionic Derivatives

Abstract: Sodium 5‐cyanotetrazolate sesquihydrate (1) was prepared from sodium azide and two equivalents of sodium cyanide under acidic conditions. Sodium 5‐cyanotetrazolate sesquihydrate (1) reacts with hydroxylammonium chloride to form 5‐aminohydroximoyl tetrazole (2). 5‐Aminohydroximoyl tetrazole (2) is treated with sodium nitrite and hydrochloric acid to form 5‐chlorohydroximoyl‐tetrazole (3). The chloride azide exchange yields 5‐azidohydroximoyl‐tetrazole monohydrate (4). When compound 4 is treated with hydrochlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…The guanidine carbon atom signal can be found at δ =158.4 ppm and 159.3 ppm for the guanidinium ( 12 ) and aminoguanidinium ( 13 ) derivatives, respectively. The assignments are in agreement to those previously reported in the literature for known structures such as H 4 TTP, 5,5′‐bistetrazolates, 5‐(1 H ‐tetrazolyl)‐1‐hydroxytetrazoles, and TKX‐50 . In the proton NMR spectra of all obtained salts, we do not observe signals consistent with the non‐deprotonated tetrazole moieties which indicate that we obtained only the tetra‐cationic derivatives of H 4 TTP.…”
Section: Resultssupporting
confidence: 91%
“…The guanidine carbon atom signal can be found at δ =158.4 ppm and 159.3 ppm for the guanidinium ( 12 ) and aminoguanidinium ( 13 ) derivatives, respectively. The assignments are in agreement to those previously reported in the literature for known structures such as H 4 TTP, 5,5′‐bistetrazolates, 5‐(1 H ‐tetrazolyl)‐1‐hydroxytetrazoles, and TKX‐50 . In the proton NMR spectra of all obtained salts, we do not observe signals consistent with the non‐deprotonated tetrazole moieties which indicate that we obtained only the tetra‐cationic derivatives of H 4 TTP.…”
Section: Resultssupporting
confidence: 91%
“…Herein we suggest the usage of small guanidinium cation that is able to form up to six charge-assisted hydrogen bonds. The advantage of this route is based on the fact that guanidinium cations are widely used for the synthesis of nitrogen-rich insensitive explosives [5][6][7].…”
Section: Intoductionmentioning
confidence: 99%
“…The tetrazole ring and its derivatives have attracted extensive interest because of their unique and excellent properties, such as high nitrogen content, high formation enthalpy, and good stability [8]. Among all of the strategies used to improve the detonation performance of energetic materials, the use of N-oxides is a special approach that facilitates the achievement of oxygen balance [8][9][10][11][12][13][14][15]. Fischer and his coworkers synthesized a series of 1H,1′H-5,5′-bistetrazole-1,1′-diolate (BTO) salts [8,16] and showed that the excellent performance of dihydroxylammonium 1H,1′H-5,5′-bistetrazole-1,1′diolate (TKX-50) is comparable with that of CL-20.…”
Section: Introductionmentioning
confidence: 99%